Molecular imaging, reconstruction and analysis of moving body organs, and stroke imaging and treatment : fifth International Workshop, CMMI 2017, second International Workshop, RAMBO 2017, and first International Workshop, SWITCH 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, Proceedings /: fifth International Workshop, CMMI 2017, second International Workshop, RAMBO 2017, and first International Workshop, SWITCH 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, Proceedings. (2017) - Unknown
No abstract available